Computational Prediction Study on Composite Slab Green Self-Compacting Concrete (GSCC) With Different Thickness Subjected to Flexural Load - Yu, Chee Long; Goh, Wan Inn (Recent Trends in Civil Engineering and Built Environment, 2023)
Composite slab was widely used in construction due to advantages such as easier installation, reduce in usage of concrete and etc. However, the research for composite slab fabricated with self-compacting concrete (SCC) was limited. Therefore, in this study, the structural behaviour of composite slab with 5% of palm oil fuel ash (POFA) and 2.5% of eggshell powder (ESP) was predicted through finite element method (FEM). This present study had successfully created the SCC and green self-compacting concrete (GSCC) composite slab model and analysed the structural behaviour by using ABAQUS software. Next, the convergence study and validation work had been carried out. Parametric studies were carried out with different thickness of composite slab and without mesh reinforcement. The previous study carried out by Bai et al. (2020) and Attarde (2014) were referred for validation work. The percentage difference in load was 10.3% for SCC and 1.5% for GSCC meanwhile the percentage difference in deflection was 4.56% for SCC and 6.27% for GSCC. The simulation results were verified since the percentage difference between simulation results and previous research is within 10%. For the parametric study, it showed that the ultimate load had increased from 53.1% to 99.6% when the thickness of composite slab increased from 150 mm to 175 mm and 200 mm. The ultimate load in composite slab had dropped 9.22% and 1.46% when there is no reinforcement for 175 mm and 200 mm. In conclusion, the thickness and reinforcement of composite slab does really affect the structural performance of composite slab.